Vascular deficits contributing to skeletal fragility in type 1 diabetes - Draghici, Adina E.; Zahedi, Bita; Taylor, J. Andrew; Bouxsein, Mary L.; Yu, Elaine W. (Frontiers in Clinical Diabetes and Healthcare, 2023)
Over 1 million Americans are currently living with T1D and improvements in diabetes management have increased the number of adults with T1D living into later decades of life. This growing population of older adults with diabetes is more susceptible to aging comorbidities, including both vascular disease and osteoporosis. Indeed, adults with T1D have a 2- to 3- fold higher risk of any fracture and up to 7-fold higher risk of hip fracture compared to those without diabetes. Recently, diabetes-related vascular deficits have emerged as potential risks factors for impaired bone blood flow and poor bone health and it has been hypothesized that there is a direct pathophysiologic link between vascular disease and skeletal outcomes in T1D. Indeed, microvascular disease (MVD), one of the most serious consequences of diabetes, has been linked to worse bone microarchitecture in older adults with T1D compared to their counterparts without MVD. The association between the presence of microvascular complications and compromised bone microarchitecture indicates the potential direct deleterious effect of vascular compromise, leading to abnormal skeletal blood flow, altered bone remodeling, and deficits in bone structure. In addition, vascular diabetic complications are characterized by increased vascular calcification, decreased arterial distensibility, and vascular remodeling with increased arterial stiffness and thickness of the vessel walls. These extensive alterations in vascular structure lead to impaired myogenic control and reduced nitric-oxide mediated vasodilation, compromising regulation of blood flow across almost all vascular beds and significantly restricting skeletal muscle blood flow seen in those with T1D. Vascular deficits in T1D may very well extend to bone, compromising skeletal blood flow control, and resulting in reduced blood flow to bone, thus negatively impacting bone health. Indeed, several animal and ex vivo human studies report that diabetes induces microvascular damage within bone are strongly correlated with diabetes disease severity and duration. In this review article, we will discuss the contribution of diabetes-induced vascular deficits to bone density, bone microarchitecture, and bone blood flow regulation, and review the potential contribution of vascular disease to skeletal fragility in T1D.